Implementation of Global Navigation Satellite Systems in Railway Traffic Control Systems: Overview of Navigation Systems, Application Areas, and Implementation Plans - Michał Steuer; Rafał Burdzik; François Piednoir (Applied Sciences)
This article characterizes and presents Global Navigation Satellite Systems in relation to rail transportation applications. Due to the review character of this article, a synthesis of the literature discussing issues related to the possibility of implementing satellite positioning systems in the framework of their use in the management and control of railway traffic was made. On the basis of the literature review, the area of potential implementation of Global Navigation Satellite Systems was identified, as well as assumptions regarding the architecture of such systems being defined, along with the definition of criteria for assessing the impact of the use of satellite systems on rail traffic safety. The purpose of the above is to direct the development of rail guidance and control systems to systems that enable precise localization of rail vehicles, thereby optimizing the use of rail infrastructure through the implementation of efficient and cost-effective localization systems. This article goes on to characterize existing Global Navigation Satellite Systems and future directions related to the use of new satellite constellations. The basis of this review is the last twenty years of scientific publications on the subject of research issues related to the use of satellite positioning in railway systems. Based on the review of the state of the art and the results of the analysis, it was determined that the most frequently mentioned area of use of satellite positioning systems is the European Train Control System, the functionality of which enables the implementation of the transportation process based on so-called moving block spacing. The results of this review of the current state of knowledge will direct those responsible for the development and implementation of modern systems in the direction and control of railway traffic.